A META-ANALYSIS COMPARING THE EFFICACY AND SAFETY OF TERLIPRESSIN AND OCTREOTIDE IN THE MANAGEMENT OF ACUTE VARICEAL BLEEDING - AKANKSHA MATHUR; ACHAL SHARMA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Various clinical trials have compared terlipressin and octreotide in the management of acute variceal bleed, but their results have been inconsistent. Therefore, the present meta-analysis was performed to compare the clinical efficacy and safety of terlipressin and octreotide and gather the strength of evidence regarding their use in variceal hemorrhage. Methods: Randomized control trials were identified using PubMed search engine and Cochrane clinical trial register (from 1994 to 2019). Initial hemostasis rate, rebleeding rate on the 5th day, and overall mortality rate during the study period were studied. The extracted data were analyzed using review manager 5.3 software. Odds ratio with 95% confidence intervals (CI) was estimated for the dichotomous outcomes. Results: A total of six randomized control trials were identified. Through comparisons of data for terlipressin and octreotide groups, we found no statistically significant differences in the initial hemostasis rate, rebleeding rate on the 5th day, and overall mortality rate between the different treatment approaches. Conclusion: The comparison of terlipressin and octreotide showed them to be equally effective and safe therapeutic agents in patients of acute variceal bleeding. Further, evidence from the future randomized controlled trials with higher quality and larger sample sizes is needed to confirm these findings.